Antimicrobial multi drug resistance and co-resistance patterns of Mannheimia haemolytica isolated from bovine respiratory disease cases – a three year (2009-2011) retrospective analysis - Lubbers, Brian V.; Hanzlicek, Gregg A. (My University, 2013)
Bovine respiratory disease continues to be the most important ailment of feedyard cattle. While the disease is multifactorial in nature, therapy continues to target the primary bacterial pathogens, Mannheimia haemolytica, Pasteurella multocida and Histophilus somni. A survey of records from a single diagnostic laboratory was conducted to evaluate the percentage of Mannheimia haemolytica isolates that were resistant to multiple antimicrobials and if co-resistance patterns could be detected. All susceptibility test results for Mannheimia haemolytica recovered from lung tissues of cattle were eligible for inclusion in the survey. There were no isolates over the course of the analysis that were resistant to all 6 antimicrobials, primarily due to a lack of resistance to ceftiofur. In 2009, just over 5% of isolates were resistant to 5 or more antimicrobials (pan-resistant). In 2011, over 35% of the Mannheimia haemolytica isolates were characterized as pan-resistant. Significant antimicrobial co-resistance patterns were only seen with oxytetracycline and tilmicosin; bacterial isolates that were resistant to either oxytetracycline or tilmicosin were more likely to be resistant to at least one other antimicrobial. The mechanisms by which Mannheimia haemolytica is developing multi drug resistance warrant investigation if antimicrobial utility in the therapy of bovine respiratory disease is to be preserved.
Keywords: Antimicrobial resistance; Bovine Respiratory Disease; Mannheimia haemolytica; Susceptibility testing